External and internal load during small-sided games in soccer: use or not floaters - Asian-Clemente, J. A.; Rabano-Munoz, A.; Nunez, F. J.; Suarez-Arrones, L. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The purpose of the present study was to analyze the internal and external loads on regular and floater players during standardized small-sided games (SSGs) with different numbers of players (teams of 3, 5, or 7 players). METHODS: Fifteen male semi-professional football players played different SSGs maintaining the same relative area per player. Total distance (TD), distance covered at different speeds (DC), the number of accelerations and decelerations, maximal (HRmax) and mean (HRmean) heart rate and rate of perceived exertion (RPE) were registered. RESULTS: Regular players showed greater internal and external loads in SSGs with 3 and 5 players without floaters than with floaters (ES 0.60-to-1.27). Likewise, with floaters, regular players in the SSGs with 3 performed more accelerations (ES 1.40 and 1.17) and with 7 achieved higher TD, DC>14 km/h, HRmax and HRmean (ES 0.66-to-2.79) than any other. During SSGs with 7 players the floaters showed a higher TD and decelerations than in other SSGs (ES 0.47-to-1.70), and a higher DC (0-6.9 km/h,14-17.9 km/h) and RPE than in SSGs with 3 players (ES 0.59-to-0.89). During SSGs with 5, the floaters showed a higher TD, HRmax, HRmean and RPE than in SSGs with 3 (ES 0.86-to-1.45). In all SSGs, regular players showed higher TD, DC (14-17.9 km/h), accelerations, decelerations and HRmean than floaters (ES 1.24-to-6.23). CONCLUSIONS: Coaches must carefully design SSGs because the number of players and the presence or absence of floaters can affect the external-internal load expressed.